KONSEP KURIKULUM DAN KURIKULUM PENDIDIKAN ANAK USIA DINI (PAUD) - Apriliana, Dewanti; Dwi Shalshadila, Rischa; Witdia; Yusria (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The curriculum is a crucial component of the education system, serving as a guideline for implementing learning. In Early Childhood Education (PAUD), the curriculum plays a strategic role in developing all aspects of a child's holistic development. This study aims to examine the general concept of the curriculum and its implementation in the PAUD curriculum. The method used was a literature review, reviewing various journals and related books. The results of the study indicate that the PAUD curriculum is designed based on children's developmental needs, is flexible, thematic, and play-oriented.